Digital Account as a Heritage of Law In Indonesia - Nahrowi Nahrowi; Apriyadi Romadon Pratama; Masyrofah Masyrofah; Syahrul A'dam (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
This study aims to analyze digital accounts, which have now become an inseparable part of life in the modern world, so that their existence is undoubtedly a necessity for society in general, both for primary, secondary and entertainment purposes as well as career and business support in the digital world, etc. This research is qualitative in the field of law, with a normative juridical approach. The findings in the study, namely a review of legal progress toward digital accounts, show that the existence of digital versions can answer the material status of digital accounts, which indicates the needs and demands of the community are part of progressive law on social causes in the community. Based on the legal provisions, digital accounts can be categorized into Inheritance, as inheritance items that will be divided among the heirs, but this does not apply to all accounts; there are several criteria for accounts that can become Inheritance, which means that digital accounts should now be included in the legacy, this also shows that progressive law flows, flexible and can realize the benefit of society.